UMPSA Tech Team achieves 13th Best Position in Asia Shell Eco Marathon 2024 - Naqiah, Puaad (UMPSA, 2024)
INDONESIA, 7 July 2024 - The UMPSA Tech team brought recognition to Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) on the international stage by securing the 13th best position in Asia and being crowned the second-best Malaysian team in the prototype battery category at the Shell Eco Marathon 2024.